Pengaruh Glukomanan dalam Perekat Berbasis Polyvinyl Acetate Terhadap Kuat Rekat Kayu - Wahyu Suci Rahmani; Bahruddin Bahruddin; Syelvia Putri Utami (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2026)
Polyvinyl acetate adhesive is widely used in the wood industry; however, its application still relies heavily on synthetic materials. Therefore, modification of polyvinyl acetate with glucomannan was conducted to enhance bonding strength while reducing the use of synthetic adhesives. This study aimed to analyze the effects of glucomannan concentration in the gel, glucomannan gel content, and polyvinyl alcohol content on the bonding strength of wood adhesives, as well as to determine the optimum formulation conditions. The experimental design was conducted using Box Behnken Design with 17 experimental runs, and optimization was performed using Response Surface Methodology. Glucomannan gel was blended with polyvinyl acetate and polyvinyl alcohol, followed by testing of dry bonding strength, wet bonding strength, and total solid content. The results showed that increasing glucomannan concentration in the gel decreased bonding strength, while increasing glucomannan gel content enhanced bonding strength up to an optimum level and declined at higher concentrations. The addition of polyvinyl alcohol significantly improved the bonding strength of glucomannan–polyvinyl acetate-based adhesives. The optimum conditions were obtained at a glucomannan concentration in the gel of 10% (w/w), glucomannan gel content of 31.38% (w/w), and polyvinyl alcohol content of 3.73% (w/w), resulting in a dry bonding strength of 16.97 MPa, wet bonding strength of 5.44 MPa, and TSC of 39.88%.